The initial steps of the black grouse repatriation - Pluhár, Dóra; Juhász, Lajos (Acta Agraria Debreceniensis, 2010)
The black grouse in Hungary is an extinct but a native and protected species now. In the 19th century, they used to be common in the so called Nyírség, the North-Eastern part of the Hungarian Great Plains. The project to re-patriate black grouse was started in 2005 by the Nyírség Company of Forestry. We studied the conditions of keeping and breeding black grouse from German and English specialists and we endeavoured to expand our breeding population in 2007. We also started to make a database of the whole bird stock, containing biometrical data from every individual specimen and data about the eggs (weight, length, width) and nestlings (weekly weight growth). In the future, we will continue our work to breed black grouse and re-patriate the new offspring, which will be nearby wild populations in a similar bio-geographic environment. In a few years it is hoped we will be able to accomplish a wild population in a natural habitat. Our work is now to breed these birds in captivity – similar to their natural habitat – prior to their release into the wild, in order to preserve biodiversity for our descendants through re-patriating black grouse here in Hungary as well.